The Bivariate Complete Fourth Power Exponential Distribution - Maturi, Dalal (International Journal of Applied Mathematical Research, 2013)
Amira and Mazloum (1993) studied  the Complete Fourth Power Exponential  (CFPE) distribution and its geometric and statistical properties against the normal distribution.  Maturi and Elsayigh (2009) investigated the relationship between variate values and ranks in samples   from the CFPE distribution. In this paper a bivariate version of the CFPE  distribution (BCFPE) is introduced and some of its properties are explored.